Production and Characterization of Polyclonal Antibodies Against Interferon Alpha in Mice - Mehreen Fatima; Fatima Khalid; Azra Quraishi (BioScientific Review, 2021)
The polyclonal antibodies are used extensively for research purposes in many areas of biology, such as immunoprecipitation, histochemistry, enzyme linked immunosorbent assays (ELISA), diagnosis of disease and western blots. Typically, an animal’s immune system will generate a large group of antibodies that recognize several epitopes of a particular antigen. Interferon alpha plays an important role in immune response activation and therefore is of interest in studies related to autoimmune diseases. In this paper the production of antibodies against interferon was studied in order to quantify interferon production to analyze interferon levels in autoimmune disorders in the future. For the antibody production, one month old laboratory grade mice were injected with interferon alpha in combination with a Freund’s complete adjuvant for a course of five weeks after which the antibodies were obtained in mouse serum. Confirmation of the production of anti-interferon alpha antibodies was carried out by the Elisa, immune dot blot and western blot analysis. An interferon alpha of approximately 20.5-21.5 KDa was detected in immunedot blot test.  These antibodies may be produced in these mouse models commercially and could be used in future for treatment of autoimmune diseases by managing the interferon levels in the patients.Keywords: ELISA, immune dot blot interferon, mice, polyclonal antibodiesCopyright(c) The Authors